2022
DOI: 10.1177/21582440221078856
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Career Decision-Making Process During the COVID-19 Pandemic: Opportunities and Challenges for Young People

Abstract: The COVID-19 pandemic, along with the measures taken against its spread, including quarantine, school closures, and online teaching, have affected young people’s career planning and decision-making process. This study explores their career decision-making process during the pandemic by analysing the following categories: effects the pandemic might have had on emotional, social, and professional aspects; support provided by family, school, and peers; challenges and difficulties experienced during the career pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
11
1
1
Order By: Relevance
“…The findings of this study regarding family influence show low values. These findings are not consistent with previous studies which show the significant influence of parents and family members on career choice process such as (Aryani & Umar, 2020;Humayon, et al 2018;Jemini-Gashi & Kadriu, 2022;Kazi, & Akhlaq, 2017). It is obvious that Palestinian high school students are now aware of the complexity of new reality which make them think deeply about their future career, preferring personal interests and values on family's desire.…”
Section: Discussioncontrasting
confidence: 98%
“…The findings of this study regarding family influence show low values. These findings are not consistent with previous studies which show the significant influence of parents and family members on career choice process such as (Aryani & Umar, 2020;Humayon, et al 2018;Jemini-Gashi & Kadriu, 2022;Kazi, & Akhlaq, 2017). It is obvious that Palestinian high school students are now aware of the complexity of new reality which make them think deeply about their future career, preferring personal interests and values on family's desire.…”
Section: Discussioncontrasting
confidence: 98%
“…Despite institutions’ efforts to ensure the continuity of education through online classes, the COVID-19 pandemic bore an academic impact on students, who were reported to be less motivated in learning and were experiencing dilemmas about the future of their careers ( Nell et al, 2020 ). Furthermore, Jemini-Gashi and Kadriu (2022) provided intriguing insights regarding the STS that Kosovo students received in the online learning context. The students regarded online learning as unsuitable for providing psychological, social, or professional support for career guidance and decision-making ( Jemini-Gashi and Kadriu, 2022 ).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Furthermore, Jemini-Gashi and Kadriu (2022) provided intriguing insights regarding the STS that Kosovo students received in the online learning context. The students regarded online learning as unsuitable for providing psychological, social, or professional support for career guidance and decision-making ( Jemini-Gashi and Kadriu, 2022 ). They specifically commented on their teachers’ lack of career orientation support.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Across the literature, studies have examined the impact of COVID-19 on individuals' career choices. Jemini-Gashi et al (8) have described how the current pandemic has affected young people. They sampled a total of 30 high school students, who were in the 12th grade, and reported that the participants reported themselves struggling with their career decision-making process in the times of the pandemic (8).…”
Section: Introductionmentioning
confidence: 99%
“…Jemini-Gashi et al (8) have described how the current pandemic has affected young people. They sampled a total of 30 high school students, who were in the 12th grade, and reported that the participants reported themselves struggling with their career decision-making process in the times of the pandemic (8). A series of research has examined how the pandemic has affected career choices among healthcare professionals, or those embarking on a healthcare-related career.…”
Section: Introductionmentioning
confidence: 99%